Cumulative exposure to remnant cholesterol and the risk of fragility fractures: a longitudinal cohort study - Hou, Xiaoli; Zhang, Nan; Guo, Lu; Wang, Yongheng; Zheng, Mengyi; Chen, Shuohua; Liu, Peipei; Wang, Mengqin; Li, Jia; Wu, Shouling; Tian, Faming (Frontiers in Endocrinology, 2023)
Objective To investigate the association between cumulative remnant cholesterol (cumRC) and the risk of newonset fragility fractures.This study included individuals who participated in 2006, 2008, and 2010 Kailuan health examinations.Baseline characteristics were compared between groups according to cumRC quartiles. The incidence density was calculated, and the log-rank test was used to compare the cumulative incidence. Cox proportional hazards models were used to estimate the hazard ratio (HR) and 95% confidence interval (CI), and restricted cubic spline was used to examine the possibly non-linear relation between cumRC and the risk of fragility fractures. Additional analyses were performed with stratification by age (≥ or < 65 years).Results A total of 43839 individuals were included in this study. During the median follow-up period of 10.97 years, a total of 489 fragility fractures occurred. Multivariable Cox proportional hazards regression model 3 showed that Q1 and Q4 groups versus Q2 group were associated with a higher HR of fragility fracture (HR 1.61, HR 1.38,, and restricted cubic spline regression analysis showed a nonlinear relationship between cumRC level and the risk of fragility fractures (P Overall association<0.001, P Non-linear association=0.001). While the association was significant in age <65 years group, but not in age ≥65 years group. The sensitivity analyses were consistent with the main results.Conclusions Both too high and too low cumRC levels were associated with greater risk of fragility fractures and this association was more significant in young and middle-aged people.